Selection of antihypertensive therapy in elderly patients, combination therapy: thiazide-like diuretics and calcium channel blockers - z. M. Galeyeva; A. S. Galyavich; L. V. Baleyeva; E. G. Safina; O. V. Sorokina (Российский кардиологический журнал, 2018)
The article presents data about the prevalence and expected prognosis for arterial hypertension. Emphasis is placed on the selection of antihypertensive therapy in elderly patients. The features concerning the positive effect of the calcium channelblocking agent — amlodipine, thiazidlike diuretic — indapamide retard in the form of monotherapy and a combination of the above drugs on the course and prognosis of arterial hypertension in elderly patients are investigated. A clinical example of the use of the fixed dose combination amlodipine + indapamide retard is also introduced.